Pengaruh Beban Kerja Terhadap Kinerja Karyawan Di Unit PKP-PK PT. Angkasa Pura I Cabang Bandar Udara Internsional Sultan Hasanuddin Makassar - Yusuf, M.Asnawi; Burhan, Hasdiana (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This research aims to analyze the influence of workload on the performance of employees of PT.Angkasa Pura I Sultan Hasanuddin International Airport Makassar Accident Relief and Fire Fighting Unit. The research method used is quantitative descriptive research. So the number of samples in this study was 77 people. Data collection techniques include observation, questionnaires, communication or direct interviews with employees of the Aviation Accident Relief and Fire Brigade/PKP-PK units who can provide information related to the problems to be discussed. The research results show that workload has a significant effect on employee performance at PT. Angkasa Pura 1 Sultan Hasanuddin International Airport Makassar Aviation Accident Relief and Fire Fighting Unit/PKP-PK..